2020
DOI: 10.3390/jcm9041227
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile of Biologics Used in Rheumatology: An Italian Prospective Pharmacovigilance Study

Abstract: Post-marketing surveillance activities are essential to detect the risk/benefit profile of biologic disease-modifying antirheumatic drugs (bDMARDs) in inflammatory arthritis. The aim of this study was to evaluate adverse events (AEs) in patients treated with bDMARDs in rheumatology during a prospective pharmacovigilance study from 2016 to 2018. Descriptive statistical analyses were performed to evaluate bDMARDs-related variables of patients without AEs/failures vs patients with AEs and failures. The risk profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 94 publications
7
9
0
2
Order By: Relevance
“…ADRs associated with biotech drugs occur more frequently in women, as documented in other studies conducted in Spain (82.9%) [13], the United States (75.5%) [14] and Italy (54.3-71.3%) [4,15], in agreement with the present finding. This is probably because many of the pathologies for which biotech drugs are used have a known predominance in women, including autoimmune diseases such as rheumatoid arthritis [16,17] or oncological diseases [18], which expose women to a greater probability of use and of developing ADRs.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…ADRs associated with biotech drugs occur more frequently in women, as documented in other studies conducted in Spain (82.9%) [13], the United States (75.5%) [14] and Italy (54.3-71.3%) [4,15], in agreement with the present finding. This is probably because many of the pathologies for which biotech drugs are used have a known predominance in women, including autoimmune diseases such as rheumatoid arthritis [16,17] or oncological diseases [18], which expose women to a greater probability of use and of developing ADRs.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the main biotech drugs related to ADRs were adalimumab and etanercept, in agreement with other studies [13,15,22], but the incidence per 100 patients per year was higher than that reported in Spain in patients with rheumatoid arthritis (8.1 for adalimumab and 5.1 for etanercept) [19]. The incidence in our study was determined in a general manner for all ADRs, while the Spanish study only considered serious ADRs [19].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations